Effect of Dietary Supplementation with Propylene Glycol on Blood Metabolites and Hormones of Nili-Ravi Buffalo Heifers: Effect of dietary supplementation on blood metabolites - Ghaffar, Abdul; Jamil, Huma; Zubair, Muhammad; Farooq, Muhammad; Murtaza, Ali; Ullah, Qudrat (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The current study was designed to investigate the effects of propylene glycol (PG) on blood metabolites, feed intake and fertility in buffalo heifers. For this purpose, 12 Nili-Ravi buffalo heifers were selected and divided into three groups A, B and C. Group A was kept as control while group B was supplemented with 150 g of PG and group C was supplemented with 300 g propylene glycol per animal per day for 30 days. Blood samples were taken on day 0, then 1st, 3rd, 5th and 7th week after initiation of PG supplementation. The serum glucose, triglycerides, total protein, albumin, alanine transaminase, total cholesterol, blood urea nitrogen, oestrogen and progesterone were determined. Results revealed that serum glucose level significantly (P<0.05) increased in both treated group as compared to control group. Total protein, alanine aminotransferase (ALT), albumin and progesterone concentrations increased significantly (P<0.05) in treated groups as compared to control group. In treated groups serum cholesterol, blood urea nitrogen, and triglycerides are significantly decreased (P<0.05). Based on results of the present and previous studies, it was concluded that feed supplementation of propylene glycol on blood metabolites and reproductive hormones showed remarkable changes.